The Dynamics of Mental Health Among Female Sex Workers in Buleleng Bali - Sari, Cindy Meilinda; Purnami, Luh Ayu; Anggaraeni, Lina; Robby, Krish Naufal Anugrah (Indonesian Journal of Global Health Research, 2024)
Mental health in female sex workers (FSWs) are influenced by a complex array of factors. Significant challenges impacting mental health include social pressure and unstable working conditions. This study aims to understand the influence of social stigma, working conditions, and social support on the mental health of FSWs. Method: This research utilizes a quantitative approach with a cross-sectional design. The independent variables are social stigma, working conditions, and social support, while the dependent variable is mental health. The study population consists of FSWs in Buleleng Regency, with a sample size of 120 participants selected through purposive sampling. The research instruments include the Generalized Anxiety Disorder 7 (GAD-7) scale for measuring anxiety and the Perceived Stress Scale (PSS) for measuring stress. Data analysis was conducted using Structural Equation Modeling (SEM). Social stigma has a direct and significant impact on the mental health of FSWs (β = 0,294, t-statistic=2,868, p < 0,01). Additionally, working conditions also have a significant direct effect on mental health (β = -0,343, t-statistic=4,569, p < 0,01). Social support acts as a mediator, mitigating the negative impact of social stigma and working conditions on mental health (β = -0,247, t-statistik=2,253, p < 0,01), Overall indicating that social stigma, working conditions, and social support are key factors influencing the mental health of FSWs.